DEVELOPMENT OF A SCIENTIFICALLY BASED IRRIGATION REGIMEDEVELOPMENT OF A SCIENTIFICALLY BASED IRRIGATION REGIME - B.Sh, Matyakubov,; D. E, Nurov,; M.F, Mukhammadov, (Journal of Higher Education and Academic Advancement, 2024)
At the time of year-to-year global climate change, and taking into account the water demand of cotton grown in the Bukhara region in order to prevent the decrease in productivity and quality of agricultural crops due to the lack of irrigation water compared to the crop demand, the method of seasonal irrigation using the data of the weather station. using CropWat 8.0. Based on the program, the coefficient values for the development stages of cotton were adopted based on the mechanical composition of the soil, the depth and mineralization of seepage waters. The results of scientific research carried out by scientists in cotton fields were analyzed in Kham